Vertical jumping tests in volleyball: Reliability, validity, and playing-position specifics - Sattler, T.; Sekulic, D.; Hadzic, V.; Uljevic, O.; Dervisevic, E. (The Journal of Strength and Conditioning Research, 2012)
Vertical jumping is known to be important in volleyball, and jumping performance tests are frequently studied for their reliability and validity. However, most studies concerning jumping in volleyball have dealt with standard rather than sport-specific jumping procedures and tests. The aims of this study, therefore, were (a) to determine the reliability and factorial validity of 2 volleyball-specific jumping tests, the block jump (BJ) test and the attack jump (AJ) test, relative to 2 frequently used and systematically validated jumping tests, the countermovement jump test and the squat jump test and (b) to establish volleyball position-specific differences in the jumping tests and simple anthropometric indices (body height [BH], body weight, and body mass index [BMI]). The BJ was performed from a defensive volleyball position, with the hands positioned in front of the chest. During an AJ, the players used a 2- to 3-step approach and performed a drop jump with an arm swing followed by a quick vertical jump. A total of 95 high-level volleyball players (all men) participated in this study. The reliability of the jumping tests ranged from 0.97 to 0.99 for Cronbach's alpha coefficients, from 0.93 to 0.97 for interitem correlation coefficients and from 2.1 to 2.8 for coefficients of variation. The highest reliability was found for the specific jumping tests. The factor analysis extracted one significant component, and all of the tests were highly intercorrelated. The analysis of variance with post hoc analysis showed significant differences between 5 playing positions in some of the jumping tests. In general, receivers had a greater jumping capacity, followed by libero players. The differences in jumping capacities should be emphasized vis-a-vis differences in the anthropometric measures of players, where middle hitters had higher BH and body weight, followed by opposite hitters and receivers, with no differences in the BMI between positions.